Mechanistic Links between Non-Coding RNAs and Myeloid Cell Inflammation in Atherosclerosis - Paloschi, Valentina; Winter, Hanna; Viola, Joana; Soehnlein, Oliver; Maegdefessel, Lars (Thrombosis and Haemostasis, 2019)
Inflammation plays a pivotal role in the chronicity of atherosclerotic lesion development and progression. Myeloid cells are involved in all stages of atherosclerosis development: they contribute in early phases to endothelial dysfunction and create a pro-inflammatory environment responsible for disease progression. Numerous studies over the last decade have repeatedly provided evidence for the crucial importance for different classes of non-coding ribonucleic acids (RNAs) in regulating gene expression, as well as messenger RNA and protein stability. Functional studies using tools to either over-express or inhibit these non-coding RNAs showcased strong effects on tempering vascular inflammation and atherosclerosis progression. With this current review article, we want to discuss prominent examples of non-coding RNAs, being either produced by myeloid cells or affecting their recruitment and activity in the context of vascular inflammation, atherosclerosis and consequential diseases (such as myocardial infarction and stroke). All of the discussed transcripts were thoroughly studied in mechanistic explorations, indicating that they have the capability to modulate inflammatory cascades in the vasculature during disease exacerbation.
Keywords: atherosclerosis; non-coding RNAs; vascular inflammation